Eryptosis and Malaria: New Experimental Guidelines and Re-Evaluation of the Antimalarial Potential of Eryptosis Inducers - Boulet, Coralie; Gaynor, Taylah L.; Carvalho, Teresa G. (Frontiers in Cellular and Infection Microbiology, 2021)
Erythrocytes possess an unusual programmed cell death mechanism termed eryptosis, and several compounds have been previously claimed to induce eryptosis in vitro. Malaria parasites (genus Plasmodium) reside in erythrocytes during the pathogenic part of their life cycle, and the potential of several eryptosis inducers to act as antimalarials has been tested in recent years. However, the eryptosis-inducing capacity of these compounds varies significantly between eryptosis-focused studies and malaria investigations. Here, we investigated the reasons for these discrepancies, we developed a protocol to investigate eryptosis in malaria cultures and we re-evaluated the potential of eryptosis inducers as antimalarials. First, we showed that eryptosis read-out in vitro is dependent on culture conditions. Indeed, conditions that have consistently been used to study eryptosis do not support P. falciparum growth and prime erythrocytes for eryptosis. Next, we defined culture conditions that allow the detection of eryptosis while supporting P. falciparum survival. Finally, we selected six eryptosis-inducers based on their clinical use, molecular target and antimalarial activities, and re-evaluated their eryptosis inducing capacities and their potential as antimalarials. We demonstrate that none of these compounds affect the viability of naïve or P. falciparum-infected erythrocytes in vitro. Nevertheless, three of these compounds impair parasite development, although through a mechanism unrelated to eryptosis and yet to be elucidated. We conclude that careful consideration of experimental set up is key for the accurate assessment of the eryptosis-inducing potential of compounds and their evaluation as potential antimalarials.